Conversion in the New Testament Paul and the twelve - Peace, Richard V. (Grand Rapids, MI Eerdmans, 1999)
Includes bibliographical references and indexes.
Keywords: Conversion -- biblical teaching; Christian converts -- Palestine -- biography; Bible. N.T. -- biography